Pengaruh Pengetahuan Kewirausahaan, Modal Usaha, dan Mental Berwirausaha Terhadap Minat Mahasiswa dalam Berwirausaha (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Nurlena La Besi; Moh. Amin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study was to find out how the influence of Entrepreneurship Knowledge, Business Capital, and Entrepreneurial Mentality on Entrepreneurial Interests "Studies on Students of the Faculty of Economics and Business Unisma". The variables used in this study consisted of independent variables: Entrepreneurial Knowledge, Business Capital, and Entrepreneurial Mentality. Dependent variable: Interest in Entrepreneurship. This research was conducted from February to completion at the Unisma Faculty of Economics and Business. Descriptive analysis, classical acceptance testing, and multiple regression analysis were used in the data analysis techniques of this study. The population of this study was economics students. The sample in this study was 90 students from the 2019 Batch of the Unisma Faculty of Economics and Business. The results of this study indicate that Entrepreneurship Knowledge, Business Capital, and Entrepreneurial Mentality simultaneously have a significant positive effect on Entrepreneurial Interest.Keywords: Entrepreneurship knowledge, business capital, entrepreneurial mentality, and interest in entrepreneurship.